Telenfermagem na promoção da capacidade de autocuidado pós-operatório no tratamento do câncer de mama: ensaio clínico randomizado - Santos, Cristina Poliana Rolim Saraiva dos (2023)
Breast cancer commonly occurs in women, affecting their daily lives in the most varied dimensions, and the surgical procedure is a common therapy. As the illness process exposes several weaknesses, including self-care, nurses tend to stimulate, strengthen and empower women to take care of themselves through educational interventions. In this regard, telenursing stands out, configuring itself as a strategy that uses information technology in the provision of nursing services. The objective of this study was to evaluate the effect of telenursing on promoting postoperative self-care capacity in the treatment of breast cancer. This is a Randomized Clinical Trial, carried out at the Assis Chateaubriand Maternity School of the Federal University of Ceará (MEAC/UFC), from July 2022 to August 2023, with women undergoing breast surgery for cancer, distributed into two parallel and randomized groups : intervention and control, with a 1:1 allocation according to the R software. Data collection occurred in four stages. It began in person during the preoperative period and involved all participants through the application of an instrument with sociodemographic, clinical and disease data, in addition to the Appraisal of Self-Care Agency Scale/Self-Care Capacity Assessment Scale. The second, third and fourth stages were similar, through three telephone calls, on the 1st, 5th to 7th and 30th to 40th postoperative days, for participants in both groups, with application of the scale to all, but to participants in the intervention group, guidance instruments on post-operative self-care and adherence to previously provided guidance were added. The exploratory analysis occurred using descriptive statistical tests, frequencies, means and standard deviations. For participant characteristics, the Mann Whitney U test and repeated measures ANOVA were used, conditioned on the data not adhering to the Gaussian distribution. To investigate the association between categorical variables, Pearson's Chi-square and Fisher's exact tests were used, with a significance level of 5%. The project was approved by the MEAC/UFC Research Ethics Committee and is registered in the Brazilian Clinical Trials Registry. The final sample consisted of 59 women with an average of 51 years old, with the majority coming from the capital, elementary school, mixed race, without professional activity, stable marital status, Catholic, with no personal history of cancer, but family history and comorbidities present. The average age of menarche and menopause was 13 and 50 years, respectively. The majority of tumors were invasive ductal carcinoma, luminal A, stage IIA, and mastectomy was the most commonly performed surgery. Regarding the self-care capacity measured by the scale, an average score was obtained that corresponded to “very good” to “excellent”, regardless of the location group, without statistical association with sociodemographic variables, but with higher scores among the participants in the group intervention when compared to the control group. When analyzed independently, some postoperative self-care actions were affected in both groups from baseline. With the application of the interventions, the intervention group showed less impairment than the control group. It is also clear that adherence to the guidelines was considered good, influencing these results. It is concluded that telenursing is a device capable of promoting the capacity for postoperative self-care in the treatment of breast cancer.